2005
DOI: 10.1128/aem.71.12.8214-8220.2005
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Antibodies against Each of the Three Subunits of the Bacillus cereus Nonhemolytic Enterotoxin Complex

Abstract: The nonhemolytic enterotoxin (Nhe) is one of the two three-component enterotoxins which are responsible for diarrheal food poisoning syndrome caused by Bacillus cereus. To facilitate the detection of this toxin, consisting of the subunits NheA, NheB, and NheC, a complete set of high-affinity antibodies against each of the three components was established and characterized. A rabbit antiserum specific for the C-terminal part (15 amino acids) of NheC was produced using a respective synthetic peptide coupled to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
106
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(109 citation statements)
references
References 30 publications
2
106
0
1
Order By: Relevance
“…In a study of over 100 B. cereus strains, cytotoxicity correlated well with the amount of Nhe produced but poorly with the concentration of Hbl (Moravek et al, 2006). The same group (Dietrich et al, 2005) found that mAb 1E11 raised against NheB prevented cytotoxicity in 20 out of 20 strains of B. cereus isolated from food. In a study of Bacillus thuringiensis strain 407 Cry 2 (indistinguishable from B. cereus), culture supernatants from hbl and cytK deletion mutants showed no impairment in cytotoxicity towards HeLa and Caco-2 cells (Ramarao & Lereclus, 2006), implying that Nhe was the major virulence factor.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…In a study of over 100 B. cereus strains, cytotoxicity correlated well with the amount of Nhe produced but poorly with the concentration of Hbl (Moravek et al, 2006). The same group (Dietrich et al, 2005) found that mAb 1E11 raised against NheB prevented cytotoxicity in 20 out of 20 strains of B. cereus isolated from food. In a study of Bacillus thuringiensis strain 407 Cry 2 (indistinguishable from B. cereus), culture supernatants from hbl and cytK deletion mutants showed no impairment in cytotoxicity towards HeLa and Caco-2 cells (Ramarao & Lereclus, 2006), implying that Nhe was the major virulence factor.…”
Section: Introductionmentioning
confidence: 78%
“…PAGE and Western immunoblotting were carried out as described previously (Lindbäck et al, 2004), using mAbs 1A8 (Dietrich et al, 2005) and 1C2 (Dietrich et al, 1999). Biotin-conjugated goat anti-mouse antibody was used as a secondary antibody (1 : 1000).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vero monkey kidney epithelial cells were grown under standard tissue culture conditions. Basic characteristics of the monoclonal antibody (MAb) 1E11 against NheB and rabbit antiserum (polyclonal antibody [pAb]) against NheC have previously been described (7). At a concentration of 10 g ml Ϫ1 , MAb 1E11 was able to neutralize the cytotoxic activity of the Nhe preparations used in this study.…”
Section: Methodsmentioning
confidence: 99%